PENGARUH KUALITAS PESAN IKLAN, KUALITAS PRODUK, KESADARAN MEREK TERHADAP MINAT BELI SERTA CITRA MEREK DAN SIKAP TERHADAP MEREK SEBAGAI VARIABEL INTERVENING (Studi pada Produk Bedak Wajah Viva Cosmetics di Kota Semarang) - Adisti, Prita; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2017)
This study aims to analyze the variables that affect buying interest in the face powder products Viva Cosmetics. This is based on the existence of problems on facial powder products Viva Cosmetics that decrease Brand Value, decrease Brand Share, TOM Brand and TOM Brand decline. This research uses quality factor of advertising message, product quality, brand awareness, brand image, brand attitude. These variables are considered to contribute substantially in the interest of buying consumers. The population in this study is respondents who has interest to buy face powder Viva Cosmetics in Semarang City. The sampling technique was done by accidental sampling. With the number of samples 150 respondents. This study has six hypotheses. The analysis tool used in this research is Structural Equation Modeling (SEM). The result of this research shows that the quality of advertising message have a positive effect on brand image, product quality have positive effect to brand image, brand awareness have positive effect to brand attitude, brand image have positive effect on brand attitude, brand image have positive effect on buying interest, brand attitude influence positive towards buying interest. Brand image factor is the most influential variable on buying interest.Keywords: brand ambassador, sales promotion, word of mouth, brand image, purchase decision